2020
DOI: 10.48550/arxiv.2011.02072
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Model Reduction for Multi-Scale Transport Problems using Model-form Preserving Least-Squares Projections with Variable Transformation

Abstract: A projection-based formulation is presented for non-linear model reduction of problems with extreme scale disparity. The approach allows for the selection of an arbitrary, but complete, set of solution variables while preserving the conservative form of the governing equations. Least-squares-based minimization is leveraged to guarantee symmetrization and discrete consistency with the full-order model (FOM) at the sub-iteration level. Two levels of scaling are used to achieve the conditioning required to effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
(120 reference statements)
0
3
0
Order By: Relevance
“…Projected equations are thus solved in the reduced subspace, and solutions in the physical coordinate system are recovered a posteriori. The efficacy of these models has been reported across several studies, even in aerospace propulsion applications [16][17][18][19]. A major pitfall of projection-based ROMs relies on the fact that they are highly intrusive, as they require the reformulation of associated PDEs in the low-dimensional manifold.…”
Section: Introductionmentioning
confidence: 99%
“…Projected equations are thus solved in the reduced subspace, and solutions in the physical coordinate system are recovered a posteriori. The efficacy of these models has been reported across several studies, even in aerospace propulsion applications [16][17][18][19]. A major pitfall of projection-based ROMs relies on the fact that they are highly intrusive, as they require the reformulation of associated PDEs in the low-dimensional manifold.…”
Section: Introductionmentioning
confidence: 99%
“…However, the space-time ROM in [72] was limited to Galerkin projection, which can cause stability issues [22,73,74] for nonlinear problems. It is well-studied that the LSPG ROM formulation [75] brings various benefits, such as better stability, over Galerkin projection with some known issues, such as structure preservation [76]. Furthermore, it is not clear if the space-time least-squares Petrov-Galerkin (LSPG) brings any advantage over the space-time Galerkin approach for a linear dynamical system.…”
Section: Introductionmentioning
confidence: 99%
“…Part of the challenge is due to the high computational cost of solving stiff ODEs as well as handling the ill-conditioned gradients of loss functions with respect to neural network weights (Anantharaman et al, 2020). In addition, it has been shown that stiffness could lead to failures in many data-driven modeling approaches, such as reduced order of modeling (Huang et al, 2020) and physics-informed neural networks . It was suggested that the stiffness could lead to gradient pathologies and ill-conditioned optimization problems, which leads to the failure of stochastic gradient descent based optimization (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%